(untitled) (Research, Society and Development, 2021)
In order to implement didactic proposals that arouse interest and facilitate the learning of chemical concepts in high school students the present study was to analyze the pertinence of working the contents of solutions and oxidation organized in the form of a Potentially Significant Teaching Unit (PMTU) with a Science-Technology-Society (STS) approach based on the “mineral extraction” in Brazil. The main theoretical contribution used in the present study was the Theory of Significant Learning of David Ausubel, complemented by the contributions of Marco Antonio Moreira through the PMTU. The work was guided by the questions: to what extent does the PMTU show a methodology that allows the approach of the themes with a STS approach? How do students react to didactic interventions involving problem situations? The research carried out is characterized by a qualitative, participant nature, structuring its data collection in two instruments: the researcher’s logbook and the materials made by the students. This study was carried out in a public school of the state education network in the municipality of Marau-RS with twelve students of the second year of polytechnic high school in the afternoon shift. The results of the study indicate the potentiality of the proposal, mainly for awakening students’ participation, curiosity and interest.